Model pemberdayaan masyarakat melalui pengembangan kelembagaan kelompok sadar wisata di Desa Tanjung Belit - Swis Tantoro; Yesi Yesi; Syafrizal Syafrizal; Yoskar Kadarisman; Achmad Hidir (Unri Conference Series: Community Engagement, 2019)
Tanjung Belit village, which is administratively located in the buffer zone of Bukit Rimbang Wildlife Reserve, Bukit Baling, has customary territory in the area of ​​customary forest around the conservation area and inside it which is traditionally managed by expressing local wisdom. Among the potential natural resources of Bukit Rimbang Wildlife Reserve, Baling Hill is Batu Dinding Waterfall and the Subayang river flow which has now become one of the potential tourist objects and has been designated as an ecotourism area. In recent years, ecotourism has been quite visited by surrounding communities and including the City community. Support from various parties is needed to build a sustainable ecotourism including institutional development and infrastructure. Community service activities will be carried out in Tanjung Belit Village, Kampar Kiri Hulu District, Kampar District. The target of the activity is the Village Apparatus, Community Leaders and members of the Sadar Wisata group. The purpose of service activities: 1). Identify and formulate village potential so that the community is able to become a part of developing ecotourism in Tanjung Belit Village. 2). Find a model of community empowerment in developing Tanjung Belit ecotourism that is based on culture and local wisdom. From the results of the service it was obtained that this activity went well. Enthusiastic participants were high, especially from members of the tourism conscious group Tanjung Belit Village, then ninik mamak, village officials and the community. The outreach material delivered provides enormous benefits and the discussion is very interesting, namely increasing the ability of the community to see and develop village potential, especially in the field of tourism. With the increase in public awareness, it is expected that participation from various parties, both local and private governments, will also help in providing various tourism support facilities and infrastructure so that the potential for tourism visits is higher. Thus it is also expected that in the future the economy of the community can improve through the tourism sector.